ANALISIS DETERMINAN PEMBIAYAAN BERMASALAH PADA BANK UMUM SYARIAH DI INDONESIA - Alfino Fadhlurrahman (2021)
Abstract This research suggests to learn the effects of Capital, Liquidity, Inflation, and the BI Repo Rate on Non-Performing Financing of Islamic commercial bank listed on the Financial Services Authority for the 2015-2019 period. We used secondary data from form of annual financial reports. We collected it by using documentation technique which is came from bank publication reports. We took 13 samples by applying saturated sampling. Finally, we evaluated them using panel data regression analysis . Our results indicate that capital as scored by the CAR has a negative influence to Troubled Financing (NPF). Liquidity as scored by the FDR has no influence to NPF. Inflation has no influence to NPF. BI Repo Rate has no influence to NPF. Keywords: capital, liquidity, inflation, BI Repo Rate, NPF